FORMULATION AND EVALUATION OF EFFERVESCENT GRANULES OF IBUPROFEN - AL-MOUSAWY, JINAN; AL-HUSSAINY, ZAHRAA; ALAAYEDI, MARYAM (International Journal of Applied Pharmaceutics, 2019)
Objective: The object of this investigation was to formulate and evaluate effervescent granules of ibuprofen, to increase its dissolution rate to get rapid analgesic and antipyretic effects. Methods: Five formulas (F1-F5) of effervescent ibuprofen granules were formulated by the wet granulation method. Croscarmellose sodium, powder of banana and other ingredients were used in the formulation of effervescent granules. Evaluation studies were carried out for all five formulas, these include: (compatibility study, flowability study, % of drug content, effervescent time and in vitro dissolution study). Results: The results show that the formulated granules have good flow properties with suitable bulk density for the uniting dose. FTIR study shows that there is no drug interaction with other ingredients in the formula. All five formulas have effervescent time less than 3 min, F5 show the best drug release 99.1±1 and effervescent time about 80 sec. Conclusion: Ibuprofen was successfully formulated and evaluated as effervescent granules by using a combination of croscarmellose sodium and banana powder.